Curriculum internationalization and the future of education - Dikli, Semire; Etheridge, Brian; Rawls, Richard (IGI Global, Disseminator of Knowledge, 2018)
"This book discusses the internationalized curriculum efforts in higher education and to provide insights about the experiences of instructors who transformed their college classes into internationalized ones (i-courses). It explain the steps taken to internationalize a number of courses from various disciplines, address challenges with the curriculum internationalization, and provide sample materials"--
Keywords: International education / Curricula / Handbooks, manuals, etc; Curriculum change / Handbooks, manuals, etc; Education and globalization / Handbooks, manuals, etc